ANGIOTENSIN-CONVERTING ENZYME-INHIBITOR CILAZAPRIL PREVENTS CHRONIC MORPHOLOGIC VASOSPASM IN RAT - (:unkn) unknown (ELSEVIER SCIENCE INC, 1994)
It has been shown that a long-acting angiotensin-converting enzyme inhibitor cilazapril prevents morphologic changes in arteries secondary to hypertension and endothelial damage, which are analogous to the changes in cerebral arteries following subarachnoid hemorrhage. In this study, the effect of cilazapril on chronic vasospasm was investigated on the rat femoral artery vasospasm model, and morphometric analyses were performed. Animals were divided into three groups. In group 1, femoral arteries were removed after cardiac perfusion. In groups 2 and 3, right femoral arteries were exposed to 0.1 mL autologous whole blood and wrapped with silastic cuff. Animals in group 3 received cilazapril (10 mg/kg) for 7 consecutive days. After the perfusion-fixation, femoral arteries were examined by light and transmission electron microscopy and processed for morphometric analysis. Vessels from animals in group 2 showed a significant luminal narrowing and morphologic changes throughout the vessel wall, while vessels from animals treated with cilazapril appeared nearly normal. These results suggest that cilazapril may be effective in the prevention of chronic vaso-spasm.
Keywords: ACE INHIBITORS; ANGIOTENSIN; CHRONIC VASOSPASM; CILAZAPRIL; SUBARACHNOID HEMORRHAGE; CEREBRAL VASOSPASM; ARTERIAL-WALL; SUBARACHNOID HEMORRHAGE; RENIN; REVERSAL; SYSTEMS